Literature Review on Development of Interactive E-Modules to Improve Science Learning Achievement in Elementary Schools - Nurhadi, Tri; Atmojo, Idam Ragil Widianto; Salimi, Moh (Universitas Sebelas Maret, 2026)
Advances in digital technology have led to innovative learning media such as interactive e-modules. However, the use of digital technology in elementary schools has not yet reached its full potential. This study aims to describe the characteristics of interactive e-module development and identify opportunities for innovation based on the limitations of previous research. This study employs a Systematic Literature Review (SLR) approach using the Kitchenham and Charters model to analyze six relevant articles from the 2022–2025 period. Article analysis was conducted using content analysis and thematic analysis methods. The findings indicate that interactive e-modules have a positive impact on student learning outcomes, motivation, and participation. Various development efforts have utilized structured models such as ADDIE and 4D combined with a constructivist approach. The use of multimedia and digital platforms, such as web and Android applications, has also been employed to enhance accessibility and interaction between students and instructional materials. Therefore, interactive e-modules are considered effective in improving the quality of science learning in elementary schools. Nevertheless, previous research has largely focused on basic cognitive skills and has not yet fully supported a deep learning approach. Further development is required to emphasize reflective, analytical, and exploratory activities to strengthen conceptual understanding and higher-order thinking skills in science learning at the elementary school level.